The Liquidity Effect in Bank-Based and Market-Based Financial Systems - Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2007)
This paper assesses how the financial system influences the strength of the liquidity effect in a calibrated limited participation model of the monetary transmission mechanism. The model suggests that bankbased systems should be characterized by smaller liquidity effects since monetary injections are spread out over a larger number of firms.
Keywords: E32; E52; E58; 330; limited participation; transmission mechanism; financial systems